Tissue Factor Pathway Inhibitor Reduces Experimental Lung Metastasis of B16 Melanoma - Amirkhosravi, Ali; Meyer, Todd; Chang, Jen-Yea; Amaya, Mildred; Siddiqui, Farooq; Desai, Hina; Francis, John L. (Thrombosis and Haemostasis, 2002)
The importance of tissue factor (TF) in tumor biology has been highlighted by studies suggesting its involvement in cell signaling, metastasis and angiogenesis. Since many animal studies have shown that anticoagulant therapy can reduce experimental metastasis, we studied whether the natural inhibitor of TF-mediated blood coagulation, Tissue Factor Pathway Inhibitor (TFPI), might be similarly effective. Using a murine experimental model, we found that intravenous injection of recombinant murine TFPI immediately before introduction of tumor cells reduced metastasis by 83% (P <0.001). B16 murine melanoma cells stably transfected with a TFPI expression vector exhibited reduced lung seeding following intravenous injection by 81% (P <0.001) compared with controls. No difference in primary tumor growth was observed between TFPI+ and control cells. Mice receiving intravenous somatic gene transfer of sense TFPI expression vector developed 78% fewer lung nodules than controls (P <0.05). We conclude that TFPI has significant anti-metastatic activity in this experimental model.
Keywords: TFPI; metastasis; melanoma; coagulation; tumor